1969
DOI: 10.1079/bjn19690095
|View full text |Cite
|
Sign up to set email alerts
|

Stomach function in relation to a scour syndrome in the piglet

Abstract: I . Piglets were left to suckle their dam for about z days after birth to obtain colostrum and were then divided into four groups. One group was left with the sow, the second was given a standard liquid diet based on cow's milk, the third the standard diet with lactic acid added to give a pH of 4.8, and the fourth the standard diet with the casein content increased by 50 yo.Stomach samples were removed at intervals by stomach tube for pH measurements and bacteriological investigations. The tube was used immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

1972
1972
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 3 publications
3
5
1
Order By: Relevance
“…A possible reduction in gastric pH as a result of lactic acid supplementation during this time may have had bactericidal effects against pathogenic bacteria by producing a more favourable environment for lactobacilli (Fuller, 1977) thus resulting in the improved performance observed. Although lactic acid has been shown to reduce the incidence of scours (White et al, 1969;Tsiloyiannis et al, 2001) its inclusion in the current experiment caused a reduction, albeit not significant in faecal dry matter (P > 0·05).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…A possible reduction in gastric pH as a result of lactic acid supplementation during this time may have had bactericidal effects against pathogenic bacteria by producing a more favourable environment for lactobacilli (Fuller, 1977) thus resulting in the improved performance observed. Although lactic acid has been shown to reduce the incidence of scours (White et al, 1969;Tsiloyiannis et al, 2001) its inclusion in the current experiment caused a reduction, albeit not significant in faecal dry matter (P > 0·05).…”
Section: Discussioncontrasting
confidence: 45%
“…Lactic acid has been shown to reduce the incidence of scours (White et al, 1969) and when supplied via water is reported to improve growth and food efficiency of weaner pigs (Kershaw et al, 1966). These effects may be due to a reduction in gastric pH and intestinal E. coli populations as a result of lactic acid supplementation (Jensen, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Other workers (White, Wenham, Sharman, Jones, Rattray and McDonald, 1969) have obtained similar timings for gut movements in normal pigs, but have also shown that scour was always preceded by diminishing gastric activity leading to gastric stasis. Milk has been shown to clot 15 to 30 min after ingestion .…”
Section: Nutrition Of the Early-weaned Pigletsupporting
confidence: 52%
“…White et al (1969) were able to reduce gastric pH by 1 unit using a milk-based liquid diet acidified to pH 4.8 with lactic acid. A corresponding reduction in haemolytic coliform bacteria and in duration of scour were observed.…”
Section: Organic Acids (Fermented Feed)mentioning
confidence: 99%